2010
DOI: 10.1136/jech.2009.104588
|View full text |Cite
|
Sign up to set email alerts
|

Age of diagnosis for autism: individual and community factors across 10 birth cohorts

Abstract: Background-The incidence of autism rose dramatically between 1992 and 2001, while the age at which children were first diagnosed declined. During this period the size and composition of the autism caseload has changed, but little is known about whether the factors associated with the timing of diagnosis may also have shifted. Using a multilevel analysis strategy, the individual and community-level factors associated with age of diagnosis were modelled across 10 birth cohorts of California children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
194
8
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(231 citation statements)
references
References 14 publications
18
194
8
11
Order By: Relevance
“…The late timing of Asperger diagnosis is compatible with the lack of gender difference in the Fountain study, since they only included children diagnosed between 2 and 8 years old (Fountain et al 2011). Unfortunately, their finding of a positive impact of socioeconomic status on the age of diagnosis could not be validated in the current study since we did not have this information.…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…The late timing of Asperger diagnosis is compatible with the lack of gender difference in the Fountain study, since they only included children diagnosed between 2 and 8 years old (Fountain et al 2011). Unfortunately, their finding of a positive impact of socioeconomic status on the age of diagnosis could not be validated in the current study since we did not have this information.…”
Section: Resultsmentioning
confidence: 42%
“…However, even larger studies have demonstrated inconsistent findings regarding sex differences in age of ASD diagnosis. While a study including as many as 491 females with ASD indicated a later age of diagnosis in females than males with ASD (Shattuck et al 2009), two related surveys, including 3,000 girls with ASD from the USA (Fountain et al 2011) and including 300 girls with ASD from Japan (Fujiwara et al 2011) found no sex differences in the age of diagnosis. To date, sex differences in ASD diagnosis have not been studied based on large scale samples in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The failure to find a decrease in the average age at diagnosis over time was particularly disappointing, especially because early diagnosis is important for access to appropriate education and intervention. Although several studies now suggest a decline in the age at diagnosis (18,19), considerable disparities remain. A few of these were pointed out in a review by Daniels and Mandell (32), which indicated that a general increase in awareness does not automatically lead to a decrease in diagnostic age (41).…”
Section: Discussionmentioning
confidence: 99%
“…AD can reliably be diagnosed by experienced clinicians in children 3 years old or younger (14). However, the average age at AD diagnosis varies across studies from 3.1 years (15) to 4.8 years (16) to 5.2 years (17) in accordance with sample characteristics and ascertainment methods (18,19). Parents are initially concerned about social development, but they also have worries about general delays and other specific problems (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn leads to the under-diagnosing of African American and Hispanic children with ASD [22]. A later diagnosis is associated with decreasing the impact that comes with receiving early treatment and intervention [10,11,33]. We used a Value Sensitive Design (VSD) methodology [12] to understand the underlying values that low-SES parents hold in terms of learning about their children's health in order to design the most appropriate solution (see section 2 below for more discussion on VSD termino logy).…”
Section: Introductionmentioning
confidence: 99%